2018
DOI: 10.1103/physrevb.97.134110
|View full text |Cite
|
Sign up to set email alerts
|

Onset of phase separation in the double perovskite oxide La2MnNiO6

Abstract: Identification of kinetic and thermodynamic factors that control crystal nucleation and growth represents a central challenge in materials synthesis. Here we report that apparently defect-free growth of La 2 MnNiO 6 (LMNO) thin films supported on SrTiO 3 (STO) proceeds up to 1-5 nm, after which it is disrupted by precipitation of NiO phases. Local geometric phase analysis and ensemble-averaged X-ray reciprocal space mapping show no change in the film strain away from the interface, indicating that mechanisms o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(20 reference statements)
2
4
0
Order By: Relevance
“…As plotted in Figure S5a of the Supporting Information, as the LMO layer thickness increases, we find that the V O formation energy decreases. This is consistent with previous results for other polar/nonpolar heterojunctions, such as La 2 MnNiO 6 /STO and LAO/STO . The presence of a surface V O is shown in Figure S5b of the Supporting Information to redistribute electronic charge within the LMO layer, including reducing a neighboring surface Mn 3+ to Mn 2+ …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As plotted in Figure S5a of the Supporting Information, as the LMO layer thickness increases, we find that the V O formation energy decreases. This is consistent with previous results for other polar/nonpolar heterojunctions, such as La 2 MnNiO 6 /STO and LAO/STO . The presence of a surface V O is shown in Figure S5b of the Supporting Information to redistribute electronic charge within the LMO layer, including reducing a neighboring surface Mn 3+ to Mn 2+ …”
Section: Resultssupporting
confidence: 91%
“…By contrast, the additional electronic, magnetic (in some cases), and chemical degrees of freedom in other complex oxides compared to LAO can lead to alternative mechanisms to alleviate the polar catastrophe. One example is manifested as NiO precipitation in La 2 NiMnO 6 films 1–5 nm from the STO interface and at the LaNiO 3 /STO interface . The formation of an NiO secondary phase appears to be driven by the formation of oxygen vacancies; at these polar/nonpolar interfaces, oxygen vacancy formation is favorable to reduce the magnitude of the built‐in electric field .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the magnetic properties of LNMO samples post-growth annealing processes are commonly employed [ 15 , 16 , 17 ]. Nonetheless, recent studies report the formation of the NiO phase impurities in LNMO thin films grown by MBE technique with the post-growth annealing, with apparently defect-free growth [ 18 , 19 ]. Detailed cross-sectional high-angle annular dark-field studies revealed an inverted “pyramid-like” shape morphology of the NiO precipitate, which progresses from a 2–3 nm base to a ∼10 nm wide mouth at the film surface [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, recent studies report the formation of the NiO phase impurities in LNMO thin films grown by MBE technique with the post-growth annealing, with apparently defect-free growth [ 18 , 19 ]. Detailed cross-sectional high-angle annular dark-field studies revealed an inverted “pyramid-like” shape morphology of the NiO precipitate, which progresses from a 2–3 nm base to a ∼10 nm wide mouth at the film surface [ 19 ]. The coexistence of double perovskite and NiO secondary phase is supported by first principles modeling of growth in oxygen deficient conditions with expected dissolution of inclusions during annealing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%